Ares’s Inner Conflict in the Novel That Summer Breeze by Orizuka (Study of Literary Psychology) - Nur Alifah, Ilham; Maulinda, Rerin (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
This study aims to describe the form of inner conflict felt by the character Ares, the causes of the inner conflict, and the way the character of Ares overcomes the conflict in the novel That Summer Breeze by Orizuka. This study uses a qualitative descriptive research method. The results of the study show that the most dominating forms of inner conflict in the character Ares are avoidance-avoidance conflicts as much as six data. In the research on the causes of inner conflict, the most dominating causes are driving forces and restraining forces as much as three data each. Meanwhile, Ares way of resolving conflicts is dominated by moving against other people.